2011
DOI: 10.1620/tjem.224.47
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Injury Increases Side Population Cells in the Uterine Endometrium: A Decisive Role of Estrogen

Abstract: Normal endometrial growth is essential for embryonic implantation and maintenance of pregnancy. The uterine endometrium contains stem cells that are involved in tissue regeneration. Side population cells (SP cells) are an emerging cell population that may be responsible for the regeneration process of uterine endometrium. In this study, we investigated the changes in the distribution of SP cells using a mouse model of uterine endometrial injury that was induced by peritoneal injection of lipopolysaccharide (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…Estrogen is able to increase the number of cells during endometrial injury and promote the regeneration of the uterine endometrium (23)(24)(25). In the present study, the level of E2 was significantly increased in the serum of rats with IUA compared with that in the controls, suggesting an effect of estrogen in the repair of intrauterine adhesions.…”
Section: Discussionsupporting
confidence: 55%
“…Estrogen is able to increase the number of cells during endometrial injury and promote the regeneration of the uterine endometrium (23)(24)(25). In the present study, the level of E2 was significantly increased in the serum of rats with IUA compared with that in the controls, suggesting an effect of estrogen in the repair of intrauterine adhesions.…”
Section: Discussionsupporting
confidence: 55%
“…The questions regarding the underlying mechanism of the procedure action remain unanswered, however some hypotheses have been made to explain its beneficial effect. It was hypothesized that the local injury to the endometrium in a cycle might induce proper decidualization for implantation competency . Li and Hao suggested that endometrial injury increases the expression of estradiol receptor in endometrial stroma causing changes in endometrial maturation .…”
Section: Discussionmentioning
confidence: 99%
“…Single or repeated biopsy of the thin endometrium induce an injury response that stimulates resident endometrial stem/progenitor cells to initiate a regenerative response and restore endometrial tissue homeostasis [2]. Human endometrial Side Population (SP) cells, a component of putative progenitor/stem cells, rapidly accumulated in mice endometrium during acute uterine injury induced by lipopolysaccharide (LPS) [8]. Though the acute inflammatory response may be beneficial to the endometrium, in IUA the inflammation is self-perpetuating and persists for a long period and can trigger abnormal endometrial functions to facilitate the formation of fibrosis and adhesion.…”
Section: Introductionmentioning
confidence: 99%